INTERCULTURAL COMPETENCE COMPARATIVE ANALYSIS OF TWO DEVELOPMENTAL MODELS – RELATED TO DEVELOPMENTAL LEVELS/STAGES - Vegh, Judit (PEOPLE: International Journal of Social Sciences, 2018)
Intercultural competence is currently an area of research in which new approaches and perspectives appear in large numbers every year. Given the importance of intercultural competence there is a need for a conceptual consensus within a multi-disciplinary approach.This contribution presents recent developments of Reflective Intercultural Competence Assessment (RICA) model, whose main goal is the development of intercultural skills in a second language and culture. The presentation focuses on first data analyses of the applied RICA model, with the aim to discover guidelines and directions for current and potential extended use of the model. The comparative analysis within the current developed RICA model and a model with long years of experience, the Developmental Model of Intercultural Sensitivity (DMIS), gives particular attention on stages of development in order to find guidance on practice and functioning.